2016
DOI: 10.1016/j.quageo.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the applicability of standardised growth curves for OSL dating of quartz from Haua Fteah cave, Libya

Abstract: The establishment of standardised growth curve (SGC) for equivalent dose (De) determination can substantially reduce the amount of instrument time required for OSL measurements. In this study, we investigated the applicability of SGC for the optically stimulated luminescence (OSL) signal from single grains and small aliquots of sedimentary quartz from Haua Fteah cave, in Libya. The samples exhibit large inter-grain and inter-aliquot variation in the shape of their single grain and small aliquot dose response c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 33 publications
0
52
2
Order By: Relevance
“…Douka et al (2014) made some pertinent observations about the OSL behaviour of the grains, including the following: (a) among the wide range of OSL decay curve shapes, some had much slower M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 rates of decay than others, but carry-over of OSL signal between successive measurement cycles was not problematic; (b) the majority of DRCs could be fitted with a single saturating exponential function; (c) grains show a large range of DRC shapes; and (d) some of the natural OSL signals are close to, or in, dose saturation: 6.4% of the multi-grain aliquots and 13.1% of the single grains have L n /T n ratios that lie at, or above, the saturation level of the corresponding DRC and can be classified as either saturated grains or as Class 3 ('oversaturated') grains . Li et al (2016) re-analysed the multi-grain data for HF11. Based on the observation that fewer than 5% of the measured single grains contributed >80% of the total OSL signal, they deduced that the measured OSL signal from the multi-grain aliquots arises from only one or two grains, thereby effectively making these measurements surrogate single-grain measurements.…”
Section: Sample Descriptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Douka et al (2014) made some pertinent observations about the OSL behaviour of the grains, including the following: (a) among the wide range of OSL decay curve shapes, some had much slower M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 5 rates of decay than others, but carry-over of OSL signal between successive measurement cycles was not problematic; (b) the majority of DRCs could be fitted with a single saturating exponential function; (c) grains show a large range of DRC shapes; and (d) some of the natural OSL signals are close to, or in, dose saturation: 6.4% of the multi-grain aliquots and 13.1% of the single grains have L n /T n ratios that lie at, or above, the saturation level of the corresponding DRC and can be classified as either saturated grains or as Class 3 ('oversaturated') grains . Li et al (2016) re-analysed the multi-grain data for HF11. Based on the observation that fewer than 5% of the measured single grains contributed >80% of the total OSL signal, they deduced that the measured OSL signal from the multi-grain aliquots arises from only one or two grains, thereby effectively making these measurements surrogate single-grain measurements.…”
Section: Sample Descriptionsmentioning
confidence: 99%
“…Understanding differences in single-grain dose response curves (DRCs) is important since some studies have shown that D e estimation can be dependent on the observed variation in the shape of the DRC (or characteristic saturation dose, D 0 ) (e.g., Gliganic et al, 2012;Duller, 2012;Li et al, 2016;Thomsen et al, 2016;Guo et al, 2017). Characterising the intrinsic variability of experimentally observed optically stimulated luminescence (OSL) signals from individual grains of quartz is, therefore, imperative to assess the reliability of DRCs and the resulting equivalent dose (D e ) values and ages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al . ( ) have suggested that if a significant proportion of grains in a sample yield infinite D e values (i.e. L n / T n values in the saturated region of the DRC), then this could result in a truncated D e distribution and a corresponding underestimation of true D e and age.…”
Section: Osl Datingmentioning
confidence: 99%
“…The latter value is slightly less than unity and indicates that the given dose was not recovered fully using the measurement conditions and/or the data selection criteria. Li et al (2016) have suggested that if a significant proportion of grains in a sample yield infinite D e values (i.e. L n /T n values in the saturated region of the DRC), then this could result in a truncated D e distribution and a corresponding underestimation of true D e and age.…”
Section: Sample Collection Preparation and Dose Rate Determinationmentioning
confidence: 99%